36 Mental health impact of completion of a formal civic service program on OIF/OEF war veterans with traumatic brain injury. (9th June 2015) - Lawrence, Karen; Matthieu, Monica
Abstract : Traumatic Brain Injury (TBI) has become known as the signature wound of the OIF/OEF conflicts. Mental health and psychosocial impacts of civic service on returning veterans have not been extensively studied and the differential impact on veterans with and without TBI is unknown. The Mission Continues, a national non-profit organisation, offers a 6-month volunteer opportunity for post-9/11 veterans at community-based organisations across the United States. The purpose of this study is to describe the mental health and psychosocial outcomes from an OEF/OIF veteran cohort who completed the civic service program. The Mission Continues Fellowship participants, composed of OEF/OIF veterans with and without TBI, completed pre- and post-Fellowship internet-based surveys. Computations of survey results include cross tabulations and bivariate analyses. Preliminary results indicate that 23% of fellows reported a TBI diagnosis. Statistically significant findings include fellows with TBI reporting, upon entering the Fellowship, lower levels of physical and mental functioning and perceived self-efficacy as well as more severe PTSD and depressive symptoms than their counterparts. While Fellows without TBI significantly improved, from pre- to post-Fellowship, on a multitude of psychosocial and quality of life indicators, Fellows with TBI showed significant improvement in three areas: perception of overall health, feelings of being supported by others, and feelings around self-efficacy.